Greater aortic stiffness is associated with lower hippocampal cerebrovascular reserve but not cerebral blood flow or amyloid in middle-aged and older adults - DuBose, Lyndsey E.; Boles Ponto, Laura L.; Moser, David J.; Pierce, Gary L. (Artery research, 2018)
Background Recent studies suggests cerebrovascular dysfunction precedes amyloid deposition and cognitive impairment in Alzheimer’s disease (AD). However, if functional impairments in the hippocampus, as evidenced by reduced hippocampal cerebral blood flow (CBF) during memory stimulation and cerebrovascular reserve (CVR), are associated with aortic stiffness is unknown. Therefore, we tested the hypothesis that elevated aortic stiffness would be associated with 1) lower hippocampal CBF during memory stimulation; 2) reduced hippocampal CVR; and 3) greater hippocampal amyloid burden in middle-aged/older adults (MA/O). Methods/Results Twenty-four MA/O adults (range: 55–87 years; mean ± SE: 70.0 ± 2.0 years) were recruited to undergo measures of aortic stiffness (carotid-femoral pulse wave velocity, cfPWV) and global and regional CBF using quantitative [ 15 O]water PET imaging. Regional hippocampal CBF (mL/min/ 100mL) was measured during memory recall of a learned word list. Hippocampal CVR was calculated as the percent (%) change in CBF in response to the pharmacological vasodilator, acetazolamide. Hippocampal amyloid burden was quantified using distribution volume ratio (DVR) from [ 11 C]PIB PET imaging. The following correlations were adjusted for age, MAP (cfPWV only) and education (% word recall only). Elevated cfPWV was associated with reduced hippocampal CVR (r = −0.59, p = 0.005) but not hippocampal CBF (p = 0.126) or amyloid deposition (p = 0.232). Lower successful word recall trended to be associated with elevated cfPWV (r = −0.38, p = 0.097) and reduced hippocampal CVR (r = 0.38, p = 0.087) in the present cohort. Conclusion Elevated aortic stiffness may impair the ability of the hippocampal cerebrovasculature to augment CBF independent of basal CBF. Funding support: NIH 5R01 AG03417, R03 AG047306-01, 1R21 AG043722, U54TR001356.